Preparing Stunting-Free Families: A Family-Centered Strategy for Preventing Childhood Stunting - Dyah Woro Kartiko Kusumo Wardani; Dewi Novitasari Suhaid; Kusuma Dini (AMK : Abdi Masyarakat UIKA, 2026)
Background: Indonesia remains one of the countries with the highest prevalence of childhood stunting. According to the Indonesian Ministry of Health, the national stunting prevalence declined from 24.4% in 2021 to approximately 21.5% in 2024, reflecting progress in prevention efforts. Despite this improvement, the prevalence remains above the threshold recommended by the World Health Organization (WHO), which considers a stunting prevalence below 20% as the target for effective public health control. These findings highlight the need for sustained and comprehensive interventions to accelerate stunting reduction in Indonesia. Situation analysis: Stunting remains a major public health concern in Indonesia, with a national prevalence of 21.5%, still above the WHO target of <20%. In Central Jakarta, Johar Baru is one of the priority areas for stunting reduction, with a reported 0.36% increase in identified stunting cases following improved child growth monitoring. In addition, 46 children under five at risk of stunting have been identified in Galur Village, within the service area of Johar Baru Community Health Center (Puskesmas Johar Baru). These conditions highlight the need for community-based interventions that strengthen family preparedness, improve nutrition knowledge, and promote healthy practices from the preconception period through the first 1,000 days of life to prevent stunting. Problem: Stunting remains a significant public health concern in Indonesia and requires urgent attention, as its high prevalence is strongly associated with inadequate knowledge and unhealthy behavioral practices among families. Solution: Health education is an effective strategy to improve individuals' knowledge and skills with the aim of promoting positive behavioral change and empowering them to become more independent in achieving and maintaining a healthy lifestyle. Results: The community education program on preparing stunting-free families effectively improved participants' knowledge. Among the 19 respondents who completed both the pre-test and post-test, the mean knowledge score increased from 5.4 before the intervention to 9.6 after the intervention, with the minimum score increasing from 0 to 8 while the maximum score remained at 10. These findings indicate that health education is an effective strategy for enhancing community knowledge and supporting family preparedness for stunting prevention. Conclusion: The community education program on preparing stunting-free families improved the knowledge and awareness of pregnant women and women of reproductive age regarding the importance of family preparedness for stunting prevention.